Pengaruh Pemasaran Digital dan Kesadaran Merek terhadap Niat Beli Sepatu Olahraga Lokal di Kota Makassar - Sitti Hasbiah; Ilma Wulansari Hasdiansa (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to empirically examine the influence of digital marketing and brand awareness on consumer purchase intentions for local sports shoe products in Makassar City. This study uses a quantitative approach with an associative method. The data collection technique was carried out by distributing questionnaires to 100 respondents selected using a purposive sampling technique. The collected data were then analyzed using multiple linear regression with the help of SPSS version 22 software. The results of the study indicate that digital marketing and brand awareness partially and simultaneously have a positive and significant effect on purchase intentions. The digital marketing variable provides a dominant contribution to increasing purchase intentions compared to brand awareness. The Adjusted R Square value of 0.773 indicates that the two independent variables are able to explain 77.3% of the variation that occurs in the purchase intention variable. This finding indicates that digital-based marketing strategies and increasing brand awareness are key factors in strengthening purchase intentions for local products amidst competitive market competition.